2011
DOI: 10.1590/s0103-863x2011000100006
|View full text |Cite
|
Sign up to set email alerts
|

Atribuição de estados mentais e compreensão conversacional: estudo com pré-escolares

Abstract: Resumo: A habilidade de atribuir a si próprio e ao outro estados mentais como desejos, intenções e crenças é denominada teoria da mente. Pesquisas recentes mostram relações entre aspectos da linguagem e aquisição de uma teoria da mente. Este estudo investiga as relações entre compreensão conversacional, entendida como um aspecto da pragmática da linguagem, e a atribuição de estados mentais. Participaram da pesquisa 28 crianças de quatro a seis anos, de ambos os sexos, de nível socioeconômico baixo, distribuída… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
2
5
0
3
Order By: Relevance
“…These results converge with those obtained by Maluf et al (2011), where older children also performed better on the Theory-of-Mind Scale proposed by Wellman and Liu (2004). In regard to age, this study's results are in accordance with those reported by Carpendale and Lewis (2006), Lane et al (2010) and Shakoor et al (2012).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results converge with those obtained by Maluf et al (2011), where older children also performed better on the Theory-of-Mind Scale proposed by Wellman and Liu (2004). In regard to age, this study's results are in accordance with those reported by Carpendale and Lewis (2006), Lane et al (2010) and Shakoor et al (2012).…”
Section: Resultssupporting
confidence: 92%
“…Brazilian studies (Maluf et al, 2011;Miguel--Silva, 2012;Noé, 2011;Ribas, 2011) found results similar to those presented by this study's participants. The convergence of results in studies addressing Brazilian children may indicate the interference of factors related to the cultural context in the acquisition of the theory of mind, as described by Shahaeian et al (2011).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Esse desenvolvimento parece estar relacionado à linguagem e vem sendo estudado em distintas culturas e idiomas (Antonietti, Liverta-Sempio, & Marchetti, 2006;Astington & Baird, 1995;Maluf, Gallo-Penna, & Santos, 2011;Souza, 2008). Nas pesquisas de tipo experimental a relação entre teoria da mente e linguagem é estudada, sobretudo, por meio da aplicação de tarefas de crença falsa (Domingues & Maluf, 2008;Rakh, Kornilov, Reich, Babyonyshev, & Grigorenko (2011).…”
Section: Introductionunclassified